Clinical features, risk factors, and prognostic markers of drug-induced liver injury in patients with stevens-johnson syndrome/toxic epidermal necrolysis - Zhibin Zhang; Sisi Li; Zhixiong Zhang; Kaihui Yu; Xunxin Duan; Lin Long; Shulan Zhang; Meiying Jiang; Ougen Liu (Wolters Kluwer Medknow Publications, 2020)
Background: The liver and skin are the most common organs involved in Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN). Drug reactions rarely affect both organs concurrently. The clinical features, risk factors, and prognostic markers of drug-induced liver injury (DILI) in patients with SJS/TEN are not well studied. Materials and Methods: The clinical features, risk factors, and prognostic markers of DILI in patients with SJS/TEN hospitalized at the dermatology department of our hospital from January 2009 to December 2018 were retrospectively analyzed. Results: A total of 298 patients with SJS/TEN were enrolled in this study. Of them, 40 had liver injury and the rest served as control. Causative drugs mainly included antipodagrics (xanthine oxidase inhibitors occupying 100% among antipodagrics), anticonvulsants (dibenzazepine occupying 76.92% among anticonvulsants), and traditional Chinese medicines. There was a statistically significant difference between the patients with liver injury and the control group in the history of liver disease, diabetes, and hyperlipidemia (P < 0.05). Nine of the 40 patients with liver injury died. High serum total bilirubin and creatinine levels were significantly associated with poor prognosis of DILI in patients with SJS/TEN (P < 0.05). Conclusion: DILI usually occurs in patients with SJS/TEN. Pre-existing liver disease, diabetes, and hyperlipidemia are independent risk factors for DILI in patients with SJS/TEN. High serum total bilirubin and creatinine levels may be useful prognostic markers for DILI in patients with SJS/TEN.